Structural basis for receptor binding heterogeneity of apolipoprotein E from type III hyperlipoproteinemic subjects. - Rall, S C (1982)
The three major isoforms of human apolipoprotein E (apo-E2, -E3, and -E4) are coded for by three alleles (epsilon 2, epsilon 3, and epsilon 4) which have a common genetic locus. Previously, we demonstrated that E2, E3, and E4 differ in primary structure from one another at two substitution sites, site A (residue 112) and site B (residue 158). At sites A/B, apo-E2, -E3, and -E4 contain cysteine/cysteine, cysteine/arginine, and arginine/arginine, respectively. We demonstrated that the substitution of cysteine for arginine at site B is at least partly responsible for the defective binding of apo-E2 to human fibroblast low density lipoprotein receptors, compared to the normal binding activity of apo-E3 or -E4. Subjects with the genetic disorder type III hyperlipoproteinemia are phenotypically homozygous for apo-E2, but the binding activity of apo-E to the fibroblast receptor differs considerably from one type III individual to another. We therefore undertook a partial comparative sequence analysis of apo-E2 from three type III subjects whose apo-E displayed this heterogeneity. The subject with the poorest binding apo-E2 was genotypically homozygous for an apo-E allele (epsilon 2); cysteine was found at sites A and B. The subject with the most active apo-E2 was genotypically homozygous for an apo-E allele (epsilon 2); cystine was found at site A and at a new site (site C, residue 145). The epsilon 2 allele specifies a protein that has arginine at site B (residue 158); the epsilon 2 allele specifies a protein that has arginine at site C (residue 145). Therefore, the two alleles differ from one another by cysteine/arginine interchanges at two positions, sites B and C. The third subject, whose apo-E2 displayed binding activity intermediate between the activities of the other two, was genotypically heterozygous, having one epsilon 2 allele and one epsilon 2 allele. The intermediate binding activity of apo-E2 from this subject resulted from having a mixture of severely defective apo-E (specified by epsilon 2) and slightly defective apo-E (specified by epsilon 2).